Pharmacological inhibition of centrosome clustering by slingshot-mediated cofilin activation and actin cortex destabilization - Konotop, Gleb; Bausch, Elena; Boutros, Michael; Krämer, Alwin; Raab, Marc-Steffen (Cancer research, 2016)
Centrosome amplification is a hallmark of virtually all types of cancers, including solid tumors and hematologic malignancies. Cancer cells with extra centrosomes use centrosome clustering (CC) to allow for successful division. Because normal cells do not rely on this mechanism, CC is regarded as a promising target to selectively eradicate cells harboring supernumerary centrosomes. To identify novel inhibitors of CC, we developed a cell-based high-throughput screen that reports differential drug cytotoxicity for isogenic cell populations with different centrosome contents. We identified CP-673451 and crenolanib, two chemically related compounds originally developed for the inhibition of platelet-derived growth factor receptor β (PDGFR-β), as robust inhibitors of CC with selective cytotoxicity for cells with extra centrosomes. We demonstrate that these compounds induce mitotic spindle multipolarity by activation of the actin-severing protein cofilin, leading to destabilization of the cortical actin network, and provide evidence that this activation is dependent on slingshot phosphatases 1 and 2 but unrelated to PDGFR-β inhibition. More specifically, we found that although both compounds attenuated PDGF-BB-induced signaling, they significantly enhanced the phosphorylation of PDGFR-β downstream effectors, Akt and MEK, in almost all tested cancer cell lines under physiologic conditions. In summary, our data reveal a novel mechanism of CC inhibition depending on cofilin-mediated cortical actin destabilization and identify two clinically relevant compounds interfering with this tumor cell-specific target. Cancer Res; 76(22); 6690-700. ©2016 AACR.
Gesehen am 29.05.2019